Transfer of rosuvastatin into breast milk: liquid chromatography–mass spectrometry methodology and clinical recommendations - Lwin EMP; Leggett C; Ritchie U; Gerber C; Song Y; Hague W; Turner S; Upton R; Garg S (Dove Medical Press, 2018)
Ei Mon Phyo Lwin,1 Catherine Leggett,2 Usha Ritchie,2 Cobus Gerber,1 Yunmei Song,1 William Hague,3,4 Sean Turner,2 Richard Upton,1 Sanjay Garg11School of Pharmacy and Medical Sciences, University of South Australia, Adelaide, SA 5000, Australia; 2SA Pharmacy, Women’s and Children’s Hospital, North Adelaide, SA 5006, Australia; 3Robinson Research Institute, University of Adelaide, SA 5006, Australia; 4Obstetric Medicine, Women’s and Children’s Hospital, North Adelaide, SA 5006, AustraliaIntroduction: Rosuvastatin reduces concentrations of total cholesterol (TC) and is used for the management of hypercholesterolemia and prevention of acute coronary syndromes. There are no published reports estimating infant exposure to rosuvastatin through breast milk.Purpose: The aims of this study were to quantify concentrations of rosuvastatin in human milk and plasma from a lactating woman taking rosuvastatin and to investigate potential infant exposure.Materials and methods: A 38-year-old breastfeeding mother was commenced on rosuvastatin 20 mg daily for secondary prevention of an acute coronary syndrome. Eight maternal breast milk samples and a single plasma sample were collected over a 24-hour period. The samples were quantified using a sensitive liquid chromatography–mass spectrometry (LC-MS/MS) method.Results: The average concentration of rosuvastatin in breast milk was 30.84 ng/mL, and a peak concentration of 58.59 ng/mL occurred at 17 hours after oral administration. Although the milk-to-plasma (M/P) ratio was 16.49 at 14 hours, the theoretical infant dosage (TID) and relative infant dose (RID) were 0.005 mg/kg/day and 1.50%, respectively.Conclusion: The findings suggest that only small amounts of rosuvastatin pass into breast milk. Should the maternal condition necessitate treatment, consideration could be given to the use of rosuvastatin during breastfeeding provided the infant is monitored.Keywords: rosuvastatin, LC-MS/MS, human plasma, human milk, lactation